Development of a real-time monitoring system for soil moisture and matric potential - HAO Pingping; HAN Jinzhao; DING Fan; SONG Lei; LI Liuke; MA Ning; ZHANG Xiaobin; FENG Junjie (Guan'gai paishui xuebao)
【Objective】Real-time monitoring of soil water content and matric potential is crucial for optimizing agricultural management. Traditional tensiometers require manual readings and frequent maintenance, which limits their scalability. This paper presents a novel system we designed for real-time and online monitoring of soil water content and matric potential.【Method】Soil water content and soil matric potential were simultaneously measured in a field. Four methods were used to calculate their relationship: the van Genuchten (V-G) model, support vector regression (SVR) model, polynomial regression model, and bayesian regression model. The accuracy of each model was evaluated against experimental data. The software and hardware of the monitoring system were designed based on a three-layer Internet of Things (IoT) architecture.【Result】① The V-G model was most accurate in describing the relationship between soil water content and matric potential, with a R2 of 0.98. It accurately captures the nonlinear characteristics of soil retention curves and is suitable for predicting soil moisture dynamics in the field. ② Based on the V-G model, the soil water content monitoring system was integrated with the AIR780E microcontroller, XGZP6895D digital barometric pressure sensor and a 4G communication module, to provide fast transmission rate and more stable connection. This is particularly useful in remote areas with complex environments. The new system is more stable than the conventional wireless communication protocols, enabling real-time data acquisition, remote transmission and online monitoring.【Conclusion】Test results indicate that the new system is stable and reliable for real-time, online soil water content monitoring. It holds promise for improving irrigation efficiency and agricultural water resource management.